Post-conflict reconciliation and development in Nicaragua: The role of cooperatives and collective action - Peter Utting; Amalia Chamorro; Christopher Bacon (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper examines how cooperatives affected and were affected by the profound political, economic and social transitions that have occurred in Nicaragua in recent decades. It pays particular attention to the shift from the post-revolutionary Sandinista regime of the 1980s to the "neoliberal" regime of the 1990s and early 2000s. In the early 1990s, a peace accord ended years of civil war and the Sandinista government was voted out of office by a coalition of Centrist and Right-wing parties. This meant that policies supporting state and cooperative forms of production were replaced by those favouring privatization, the rolling back of the state and the freeing up of market forces. Cooperatives and the agrarian reform process initiated by the Sandinista government were heavily impacted by this process, often in contradictory ways. Land redistribution to landless peasant farmers and cooperative organizations continued as part of the process of peace-building prior to the elections. Demobilized military and other security personnel were given land after the elections. Workers in state-owned farms and agro-industrial enterprises also acquired assets when part of the state sector was converted to worker-owned and managed enterprises. But the neoliberal era ushered in a process of decollectivization and dispossession and heavily constrained access to credit and support services for cooperatives and small-scale farmers. Agricultural workers and producers were not passive bystanders in this process. Their responses conformed to a Polanyian-type "double movement" where societal forces mobilize in myriad ways to protect against the negative social effects of economic liberalization and the dominance of market forces. The pro-market strand of the double movement centred not only on economic liberalization but also an agrarian counter-reform centred on decollectivization and returning lands to former owners. The societal reaction or "protective" strand of the double movement consisted of diverse forms of contestation, collective action and social innovation. Divided in three parts, this paper first outlines the rapid rise of the cooperative sector and its strengths and weaknesses during the post-revolutionary period from 1979 to the electoral defeat of the Sandinistas in 1990. Part 2 examines the uneven trajectory of agrarian reform and cooperative development during the neoliberal 1990s, consisting of counter reform and ongoing redistribution to the landless. Part 3 examines four manifestations of the "double movement" by agricultural workers and producers. They include (i) the proliferation of civil and armed resistance in the early 1990s; (ii) the structuring of a cooperative movement; (iii) efforts to empower small coffee producers via the fair trade movement and the "quality revolution" and (iv) the drive to reactivate the smallholdings of poor rural women and organize them in pre-cooperative groups. A concluding section distils the main findings for the addressing the challenge of post-conflict reconciliation and development, and refers briefly to the implications for the cooperative movement of the return to power of the Sandinista National Liberation Front in 2007. The main policy lesson for governments engaged in processes of peace-building and "post-conflict" reconstruction would seem to be: ignore the issue of inclusive agrarian development at your peril! If a disabling policy environment exists, and if demands for land and employment on the part of subaltern groups are not met, various forms of resistance will ensue, with the possibility of renewed violent conflict and the inability to govern effectively. And when a political party seemingly supportive of the cooperative sector regains the reins of power, renewed support may come at the cost of dependency and loss of autonomy of the cooperative movement.
Keywords: 330